Evaluasi Program Parenting Penguatan Karakter Integritas Sejak Dini Dirumah - Nelly Agustina; Yunita Iswahyuni; Noviyanti Tarigan; Dinda Arifin (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Character education is an essential aspect of early childhood development, particularly in fostering integrity, which includes honesty, responsibility, discipline, commitment, and consistency between words and actions. As the child's first educational environment, the family plays a strategic role in cultivating integrity values through well-planned and sustainable parenting programs. Therefore, evaluating parenting programs is necessary to determine their effectiveness and provide a basis for continuous program improvement. This study aims to analyze the evaluation of parenting programs in strengthening children's integrity character at home through a literature review approach. The study employed a qualitative design by examining scientific journal articles, academic books, policy documents, and previous research related to parenting, character education, integrity, program evaluation, and early childhood education. Data were analyzed using content analysis involving identification, classification, interpretation, and synthesis of findings from the reviewed literature. The findings indicate that the effectiveness of parenting programs is influenced by the alignment of program objectives with family needs, parents' readiness as primary educators, consistency in implementing character-building habits at home, and continuous evaluation of children's behavioral development. Sustainable parenting programs enhance parental involvement in character education, strengthen the habituation of integrity values in daily life, and promote effective collaboration between families and educational institutions. Furthermore, program evaluation provides comprehensive information regarding the strengths, weaknesses, opportunities, and challenges of parenting implementation, serving as a foundation for continuous improvement. Therefore, evaluating parenting programs is an effective strategy for strengthening integrity character in early childhood within the family environment